Improving children's fundamental movement skills through a family-based physical activity program: results from the "Active 1 + FUN" randomized controlled trial - Amy S. Ha; Chris Lonsdale; David R. Lubans; Florrie F. Ng; Johan Y. Y. Ng (BMC, 2021)
Abstract Background Physical activity is related to many positive health outcomes, yet activity levels of many children are low. Researchers have suggested that family-based interventions may improve physical activity behaviors of both children and their parents. In this study, we evaluated the "Active 1 + FUN" program, which was designed based on tenets of self-determination theory. Intervention components included free sporting equipment, ten coach-led workshops and activity sessions, and one booster session. Methods We evaluated the intervention program using a randomized controlled trial. One hundred seventy-one families were randomly allocated to either an experimental group or a wait-list control group. Participants were exposed to program contents over a nine-month period, while families in the control did not receive any form of intervention. Measured constructs included moderate-to-vigorous physical activity, co-physical activity behaviors, fundamental movement skills, BMI, and several self-reported questionnaire outcomes. Hierarchical linear modeling was used to compare changes in measured outcomes across the two groups. Results No significant intervention effects were found for children's and parents' accelerometer-measured moderate-to-vigorous physical activity, or their co-physical activity. However, in terms of children's fundamental movement skills, a significant Time*Group interaction (B = 0.52, 95% CI [0.07, 0.96] for Times 1 to 2; B = 0.24, 95% CI [0.01, 0.48] for Times 1 to 3) in favor of the experimental group was found. Conclusions Results suggested that the "Active 1 + FUN" program was effective in improving children's fundamental movement skills. Additional research is needed to examine how family-based initiatives could effectively improve physical activity behaviors too. Trial registration ANZCTR, ACTRN12618001524280. Registered 11 September 2018, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=375660 .